Exogenous salicylic acid alleviates the negative impacts on production components, biomass and gas exchange in tomato plants under water deficit improving redox status and anatomical responses. Issue 2 (16th January 2021) - Lobato, Allan Klynger da Silva; Barbosa, Maria Antonia Machado; Alsahli, Abdulaziz Abdullah; Lima, Emily Juliane Alvino; Silva, Breno Ricardo Serrão da
Abstract: Salicylic acid (SA) is an interesting messenger in plant metabolism that modulates multiple pathways, including the antioxidant defence pathway, and stimulates anatomical structures essential to carbon dioxide fixation during the photosynthetic process. The aim of this research was to determine whether pre‐treatment with exogenous SA can alleviate the deleterious effects induced by water deficit on production components, biomass and gas exchange, measuring reactive oxygen species, antioxidant enzymes, variables connected to photosynthetic machinery, anatomical responses, and agro‐morphological traits in tomato plants under water deficit. The experiment used a factorial design with four treatments, including two water conditions (control and water deficit) and two salicylic acid concentrations (0 and 0.1 mM salicylic acid). Water deficit negatively impacted the biomass and fruit number of tomato plants. Pre‐treatment using 0.1 mM SA in plants submitted to water restriction induced increments in fruit number, weight, and biomass. These results were related to the protective role triggered by this substance, stimulating superoxide dismutase (27.07%), catalase (17.81%), ascorbate peroxidase (50.52%), and peroxidase (10.81%) as well as reducing the cell damage (malondialdehyde and electrolyte leakage) caused by superoxide and hydrogen peroxide. Simultaneously, application of SA improved the net photosynthetic rate (84.55%) and water‐use efficiency (65.00%) of stressed plants in which these factors are connected to anatomical benefits, as verified by stomatal density, palisade and spongy parenchyma, combined with improved performance linked to photosystem II.